Asymptomatic bacteriuria and associated host factors in Diabetic patients with special reference to UTI Chromagar - Divyashree K; Kala Yadhav M L (International Journal of Medical Research and Review, 2015)
Introduction: To study the prevalence of asymptomatic bacteriuria (ASB) in diabetics compared to non-diabetics and to determine the associated host factors responsible for ASB in diabetics.Materials and Methods: 250 diabetics and 100 controls were enrolled in the study and were screened for ASB using semi-quantitative culture methods and UTIchrom agar. The samples were screened for glucosuria, ketonuria and pyuria.Results: ASB was more common in diabetics compared to non-diabetics(12.8% v/s 6% ) and the increase was more in female diabetics when compared to female non-diabetics(16% v/s 6.15%) whereas male counterparts did not show much difference from the non-diabetics (6.09% v/s 5.71%). There was significant influence of age, duration of diabetes, glucosuria, ketonuria, proteinuria and pyuria on the incidence of ASB in diabetics thus proving them as possible risk factors for development of ASB. E.coli was the most common organism found in both diabetic as well as non diabetic cases of ASB (40.6% and 57.14% respectively). The next frequent organisms were Klebsiella and Staphylococcus. The sensitivity pattern was similar in both the population with ASB. Culture on UTI CHROMagar yielded quicker results when compared to standard culture methods.Conclusion: ASB is almost 3 times more common in female diabetics compared to female non-diabetics whereas there is not much difference among the male counterparts. The risk factors for ASB in diabetics included age, longer duration of diabetes, poor glycaemic control and renal dysfunction indicated by proteinuria. Culture on UTI CHROMagar is an easy and faster means of identification of organisms.